The reliability of a restraint sensor system for the computer-supported detection of spinal stabilizing muscle deficiencies. - Pfeifle, C.; Edel, M.; Schleifenbaum, S.; Kuhnapfel, A.; Heyde, C. E. (BMC Musculoskelet Disord, 2020)
BACKGROUND: The presence of muscular deficiency seems to be a major cause of back pain that requires counteractions. Considering that the autochthonous back muscles, responsible for straightening and stabilizing the spine, cannot be activated voluntarily, they can be strengthened only through specific training. The computer-supported test and training system (CTT) Centaur (BfMC GmbH, Leipzig, SN, Germany) seems well suited for this purpose. To show its potential as a reliable diagnostic and training tool, this study aimed to evaluate the test-retest reliability of this 3D spatial rotation device. METHODS: A prospective pilot study was conducted in 20 healthy volunteers of both sexes. For test-retest reliability analysis, three measurements were performed with a two-day interval between each measurement. Each measurement consisted of a one-minute endurance test performed in eight different positions (transverse plane). During the test, the subject was tilted by 90 degrees in the sagittal plane from a neutral, upright position. Meanwhile, the subject's level of upper body stabilization along the body axis was assessed. All trunk movements (momentum values) were quantified by a multicomponent force sensor and standardized relative to the subject's upper body mass. The range of motion was assessed by 95% confidence ellipse analysis. Here, all position-specific confidence ellipses for each measurement were merged to a summarized quantity. Finally, ICC analysis using a single-rating, absolute agreement, two-way mixed-effects model and a Bland-Altman plot was performed to determine the reliability. RESULTS: Considering all measurements (t1, t2, t3), the ICC for reliability evaluation was 0.805, and the corresponding 95% confidence interval (CI) was [0.643, 0.910]. Moreover, the Bland-Altman plots for all three pairs of time points did not show significant differences. CONCLUSION: This study concludes that the CTT Centaur shows good test-retest reliability, indicating it can be used in clinical practice in the future.
Keywords: *Computers; Female; Germany; Humans; Male; *Muscles; Pilot Projects; Prospective Studies; Reproducibility of Results